Corruptive Factors in Local Government (Case of St. Petersburg) - V. A. Semenov; V. V. Ereshkin (Управленческое консультирование)
In the new history of present states, one of the main risks to the socio-economic development of society is corruption. The fight against it is based on the development of normative and legal acts, prevention and prevention, information and investigative activities, and is expressed in the form of deterrence and counteraction.The fundamental regulatory framework is the “United Nations Convention against Corruption” (adopted in New York on October 31, 2003 by Resolution 58/4 at the 51st plenary session of the 58th UN General Assembly), the Federal Law “On Countering Corruption” of 12/25/2008 N 273-FL. At the same time, to date, combating corruption in local government is regulated superficially and is formal in character. Due to the actual closed nature of the activities and peculiarities of the functioning of local government, the issues of corruption are not fully studied in order to provide effective prevention and counteraction.The possibility of a detailed study of corruptionogenic factors of local government and the development of methods of counteraction became possible after the elections of 2019, after which non-systemic municipal deputies were elected to the representative bodies of local government. Exercising the powers in the representative body of local government, municipal deputies independent from the territorial executive bodies of state power were able to study the specifics of the functioning of local government, make public the issues of the problem field, identify vulnerable places in the activities, take response measures and make appropriate practical conclusions.The purpose of this article is to establish the causes of the emergence of corruption in local government on the example of a separate municipality of the MO Svetlanovskoye of St. Petersburg. Study of the causes of the emergence of corruptionogenic factors, search and proposal of possible ways to address the issue of effective counteraction to corruption in local government in the new conditions of life of modern society.On the basis of the study the authors declare the need to take specific measures of response of the public authorities of the subject of the Russian Federation and the representative body of local government, aimed at creating certain conditions for effective counteraction and prevention of corruption, minimizing the consequences of corruptogenic factors in the modern conditions of democratic functioning of local government.